Akhlaq dan Hukum Islam: Strategi Efektif dalam Mengatasi Korupsi dan Membangun Negara - Kusyana, Kusyana; Romlah, Romlah; NaufalFalih, Imam (Fakultas Hukum dan Ekonomi Syariah Institut Agama Islam Pangeran Dharma Kusuma Indramayu, 2024)
Ethics and Islamic law play a crucial role in shaping morality and legal order within Muslim societies. In the context of corruption and nation-building, effective strategies that integrate ethical values and principles of Islamic law are pertinent. This article explores key concepts in Islamic ethics and law, analyzing how the implementation of such strategies can combat corruption and advance national development. By considering ethical and legal aspects in Islam, this research underscores the importance of a holistic approach involving education, law enforcement, and institutional development in fostering a just and integrity-driven society.The findings indicate that integrating Islamic ethical values and law is effective in combating corruption by promoting honesty, integrity, and accountability. These values reduce corrupt practices and foster public trust, while Islamic law imposes stringent sanctions on corrupt individuals. However, implementation faces challenges such as resistance, societal awareness deficits, and legal complexities. The solution lies in collaborative efforts among governments, anti-corruption agencies, religious institutions, academics, and communities to address these challenges effectively.